The utility of strain elastography in differentiation between healthy thyroid parenchyma and residual/recurrent thyroid parenchyma disorders - Gül, Yeliz; Kılıçarslan, Gülhan; Özkan, Zeynep; Balaban, Mehtap (The European Research Journal, 2022)
Objectives: This study is designed to evaluate the utility of strain elastography in the differentiation between healtly thyroid parenchyma and residual/recurrent thyroid parenchyma after partial thyroidectomy. Methods: Gray-scale ultrasonography (B-mode US) and strain elastography were performed in patients who had undergone partial thyroidectomy due to benign thyroid diseases and volunteers as a control group without any throid disease. The elasticity scores and strain rate values of thyroid parenchyma were obtained in two groups and compared. The strain elastography of the patient and control groups were analyzed with the Pearson Chi-Square test. Strain rates for both groups were compared with the Manny-Whitney U test. Ethical approval and permissions were obtained from legally authorized representatives and patients. Results: There were 94 cases in total, 47 cases (4 male, 43 female; mean age: 51 ± 12.9 years, ranging between 25-79) in the patient group and 47 cases (11 male, 36 female; mean age: 36.8 ± 11.5 years, ranging between 19-71) in the control group. The strain rate of the right (2.22 ± 1.9) and left thyroid lobe (1.9 ± 1.9) were significantly higher than control group (1.05 ± 0.6 and 0.8 ± 0.5, respectively; p = 0.002 and p = 0.043). Conclusions: The elasticity of thyroid parenchyma after partial thyroidectomy differs from healthy thyroid tissue, which may be helpful in differentiation between residual parenchymal changes in thyroid from malignant lesions with strain elastography.